Plant Extracts and Phytochemicals Targeting α-Synuclein Aggregation in Parkinson's Disease Models - Javed, Hayate; Nagoor Meeran, Mohamed Fizur; Azimullah, Sheikh; Adem, Abdu; Sadek, Bassem; Ojha, Shreesh Kumar (Frontiers in Pharmacology, 2019)
-Synuclein (-syn) is a presynaptic protein that regulates the release of neurotransmitters from synaptic vesicles in the brain. -Syn aggregates, including Lewy bodies, are features of both sporadic and familial forms of Parkinson’s disease (PD). These aggregates undergo several key stages of fibrillation, oligomerization, and aggregation. Therapeutic benefits of drugs decline with disease progression and offer only symptomatic treatment. This requires novel therapeutic strategies, which can either prevent or modify the disease process. The link between -syn and the etiopathogenesis and progression of PD are well established in the literature. Studies indicate that -syn is an important therapeutic target and inhibition of -syn aggregation, oligomerization, and fibrillation are an important disease modification strategy. However, recent studies have shown that plant extracts and phytochemicals have neuroprotective effects on -syn oligomerization and fibrillation by targeting different key stages of its formation. Although many reviews on the antioxidant-mediated, neuroprotective effect of plant extracts and phytochemicals on PD symptoms have been well highlighted, the antioxidant mechanisms show limited success for translation to clinical studies. The identification of specific plant extracts and phytochemicals that target α-syn aggregation will provide selective molecules to develop new drugs for PD. The present review provides an overview of plant extracts and phytochemicals that target -syn in PD and summarizes the observed effects and the underlying mechanisms. Furthermore, we provide a synopsis of current experimental models and techniques used to evaluate plant extracts and phytochemicals. Plant extracts and phytochemicals were found to inhibit the aggregation or fibril formation of oligomers. These also appear to direct -syn oligomer formation into its unstructured form or promote nontoxic pathways and suggested to be valuable drug candidates for PD and related synucleinopathy. Current evidence from in vitro studies require confirmation in the in vivo studies. Further studies are needed to ascertain their potential effects and safety in preclinical studies for pharmaceutical/nutritional development of these phytochemicals or dietary inclusion of the plant extracts in PD treatment.